Wood Gasification Biochar as an Effective Biosorbent for the Remediation of Organic Soil Pollutants - Elisabetta Loffredo; Nicola Denora; Danilo Vona; Antonio Gelsomino; Carlo Porfido; Nicola Colatorti (Soil Systems)
A biochar (BC) generated by the pyrogasification of wood chips from authorized forestry cuts was extensively characterized and evaluated for its efficacy in retaining/releasing two agrochemicals, namely the fungicide penconazole (PEN), the herbicide S-metolachlor (S-MET), and the xenoestrogen bisphenol A (BPA) widely present in industrial effluents. The elemental composition of BC was evaluated using CN elemental analysis and total reflection X-ray fluorescence (TXRF) spectroscopy which showed the abundance of elements typically found in BCs (Ca, K, P) along with essential trace elements such as Fe and Mn. Scanning electron microscopy coupled with energy-dispersive X-ray analysis (SEM-EDX) described the surface features of BC along with the major surface elements, while Brunauer–Emmett–Teller (BET) analysis revealed, as expected, a large specific surface area (366 m2 g−1). High porosity (0.07 cm3 g−1) was demonstrated by the density functional theory (DFT) method, while Fourier transform infrared (FT-IR) spectroscopy highlighted the presence of a prominent aromatic structure and the abundance of reactive functional groups responsible for the binding of the compounds. The sorption/desorption capacity of BC was studied by means of sorption kinetics and isotherms in batch trials, and by modeling the experimental data with various theoretical equations. All compounds reached sorption equilibrium on BC very rapidly, following preferentially pseudo-second-order kinetics. Freundlich adsorption constants of PEN, S-MET, and BPA were 37.3, 13.2, and 11.6 L g−1, respectively, thus demonstrating the great affinity of BC for hydrophobic pollutants. The adsorption process was hysteretic as only a small fraction of each compound was slowly desorbed from BC. The overall results obtained highlighted the great potential of BC of acting as a biosorbent of contaminants, which is of great importance for the containment of pollution in agricultural soils and for limiting the entry of toxic compounds into the human and animal food chain.